The Tet offensive - Rice, Earle, Jr., 1928- (San Diego : Lucent Books, 1997)
Describes the planning, execution, and results of the North Vietnamese army's major offensive in the Vietnam War.
Includes bibliographical references (p. 88-91) and index.
Keywords: Tet Offensive, 1968 -- Juvenile literature; Tet Offensive, 1968.; Vietnam War, 1961-1975 -- Campaigns